Envelope proteins from clinical isolates of human immunodeficiency virus type 1 that are refractory to neutralization by soluble CD4 possess high affinity for the CD4 receptor. - Brighty, D W (1991)
Recent evidence indicates that primary clinical isolates of human immunodeficiency virus type 1 (HIV-1) require significantly more soluble CD4 (sCD4) to block infection than the prototypic laboratory strain HTLV-IIIB. The currently accepted explanation for these observations is that the envelope glycoproteins from primary clinical isolates possess lower affinities for CD4 than laboratory strains. This observation has far reaching implications for the clinical effectiveness of sCD4. To test whether the resistance of clinical isolates to sCD4 neutralization correlates with low-affinity binding to gp120, we have compared gp120 glycoproteins derived from the clinical isolates HIV-1 JR-CSF and JR-FL with those derived from the prototypic strain HIV-1 BH10 in quantitative sCD4 binding studies. Surprisingly, our results demonstrate that gp120 derived from HIV-1 JR-CSF and JR-FL possess sCD4 binding affinities of equal or greater magnitude than gp120 derived from HIV-1 BH10. Thus primary clinical HIV-1 isolates can and do possess gp120 with high affinity for CD4, and sensitivity to neutralization by sCD4 is dependent upon factors other than the intrinsic affinity of gp120 for CD4.